The Limits of Homogenization: What Hydrological Dynamics can a Simple Model Represent at the Catchment Scale?. Issue 6 (8th June 2021) - Wen, Hang; Brantley, Susan L.; Davis, Kenneth J.; Duncan, Jonathan M.; Li, Li
Abstract: Large‐scale models often use a single grid to represent an entire catchment assuming homogeneity; the impacts of such an assumption on simulating evapotranspiration (ET) and streamflow remain poorly understood. Here, we compare hydrological dynamics at Shale Hills (PA, USA) using a complex model (spatially explicit, >500 grids) and a simple model (spatially implicit, two grids using "effective" parameters). We asked two questions: What hydrological dynamics can a simple model reproduce at the catchment scale? What processes does it miss by ignoring spatial details? Results show the simple model can reproduce annual runoff ratios and ET, daily discharge peaks (e.g., storms, floods) but not discharge minima (e.g., droughts) under dry conditions. Neither can it reproduce different streamflow from the two sides of the catchment with distinct land surface characteristics. The similar annual runoff ratios between the two models indicate spatial details are not as important as climate in reproducing annual scale ET and discharge partitioning. Most of the calibrated parameters in the simple model are within the ranges in the complex model, except that effective porosity has to be reduced to 40% of the average porosity from the complex model. The form of the storage‐discharge relationship is similar. The effective porosity in the simple model however represents the dynamic and mobile water storage in the effective drainage area of the complex model that connects to the stream and contributes to high streamflow; it does not represent the passive, immobile water storage in the often disconnected uphill areas. This indicates that an additional uphill functioning unit is needed in the simple model to simulate the full spectrum of high‐low streamflow dynamics in natural catchments. Key Points: A simple, lumped model can reproduce annual scale discharge, evapotranspiration and daily scale peak streamflow (flooding) but not low streamflow (droughts) Water storage in the simple model represents the dynamic storage that is connected to the stream in the complex, spatially explicit model An additional uphill, often disconnected functioning unit in the simple model may help represent the full spectrum of high‐low streamflow dynamics